(untitled) (Al-Mansour Journal, 2022)
Iraq’s economy is suffering from problematic imbalances and extensive internal and external reasons, , it is still the economy yield (unilateral) despite the availability of numerous and varied resources and the existence of good potential in it, and the diversification of the economy process and directed towards the direction that serves the economic development process is very important. attempts to processing imbalance in the Iraqi economy was incomplete and did not clear and accurate, too, as well as the lack of clarity in the development plans of economic sectors, which resulted in a waste of wealth and loss and the lack of significant growth and evolution over the past years. So it must adopt appropriate and effective strategy for the case of the Iraqi economy and basic sectors while providing an appropriate environment for it, in the introduction develop these plans and arrange the investment priorities and infrastructure, and diversify the Iraqi economy to ease the dependence on the oil sector and increase the contribution of other sectors. All this would lead to the achievement of economic and social development.